Clinical Significance of Right Ventricle Echocardiographic Patterns in Critically-Ill COVID–Related Acute Respiratory Distress Syndrome "On Behalf of Protecting the Right Ventricle Network (PRORVnet)". (March 2023) - Lazzeri, Chiara; Bonizzoli, Manuela; Batacchi, Stefano; Cianchi, Giovanni; Chiostri, Marco; Socci, Filippo; Peris, Adriano
We assessed whether right ventricle (RV) alterations and their development may have clinical significance in critically-ill Coronavirus Disease (COVID) patients, as detected by serial echocardiograms during Intensive Care Unit (ICU) course. This observational single center study included 98 consecutive patients with COVID-related acute respiratory distress syndrome (ARDS). Three subgroups were considered: RV Dysfunction (Dys) on admission (10/98, 10%), developed RV Dys (17/98, 17%), and no RV Dys (71/98, 73%). Overall mortality at 3 months was 46.9%. The first subgroup was characterized by the highest need for Extracorporeal Membrane Oxygenation (ECMO) support ( P < .001) and a systemic inflammatory activation (as indicated by increased D-dimer), the second one by the lowest PaO2/FiO2 (P/F). At multivariate regression analysis, age and Sequential Organ Failure Assessment score were independent predictors for mortality. Different RV echo patterns were observed in critically ill patients presenting with COVID-related ARDS during ICU stay. RV Dys on admission was characterized by a high inflammatory activation while patients who developed RV Dys during ICU stay showed lowest P/F. Both these two subgroups identify patients with a severe COVID disease which in a high percentage of cases was unresponsive to standard treatment and required the use of ECMO.